Occurrence and susceptibility profile of Candida sp in blood cultures from a university hospital - Teixeira-Loyola, Ana Beatriz A.; Fernandes, Ana Paula; Barbosa, Camila C.; Mattozo, João Marcelo A.; Silva, Adenilza C.; Schreiber, Angélica Z. (Medicina (Ribeirao Preto), 2013)
The genus Candida is responsible for hospital infections associated with fungemia, especially in critical sectors. Objectives: To evaluate the prevalence of Candida species from blood cultures of Clinical Laboratory, the HCSL Pouso Alegre, MG and evaluated the susceptibility test for anphotericin B, itraconazole, fluconazole e voriconazole. Methods: We conducted a study from July 2009 to July 2010, which evaluated all blood cultures of HCSL this period. The fungi isolated from blood cultures were identified by classical methods and for automated identification. The susceptibility test was evaluated by microdilution broth CLSI M27-A3. Results: A total of 1388 samples with 108 positive samples, and fungal 10. The fungal incidence was: Adults UTI (4), Neo UTI (5) and Male Ward (1). Were identified as Candida albicans (5) and Candida parapsilosis (4), and Candida sp (1). All samples show sensibility for antifungal tested. Conclusion: The candidemia observed in this study (1.38%) is similar to comparative studies as we have seen in the incidence in intensive care units.